Conceptual design for a new heterogeneous 241Am-9Be neutron source assembly using SOURCES4C-MCNPX hybrid simulations; Applied Radiation and Isotopes; Vol. 153 - Ghal-Eh N. Nima (2019, 2019)
Title screen